The Effect of β2-Adrenoceptor Genotype on Phenylephrine Dose Administered During Spinal Anesthesia for Cesarean Delivery. (June 2015) - Odekon, Lale; Landau, Ruth; Blouin, Jean-Louis; Brodow, David; Wang, Shuang; Smiley, Richard M.
Abstract : BACKGROUND: The β2-adrenoceptor ( ADRB2 gene) possesses several polymorphic sites that have physiologic and/or pharmacologic significance. Previous work has demonstrated that the ADRB2 genotype affects the amount of ephedrine administered to maintain blood pressure during cesarean delivery with spinal anesthesia. This study investigated whether the ADRB2 genotype affected phenylephrine dose requirements during cesarean delivery. Our hypothesis was that the ADRB2 genotype altered the ephedrine dose-response and that we would not see this effect if phenylephrine was the vasopressor used to maintain blood pressure because phenylephrine does not act via the β2-adrenoceptor. METHODS: Women undergoing elective cesarean delivery were studied. Baseline systolic blood pressure (SBP) was determined, and spinal anesthesia was initiated with hyperbaric bupivacaine 12 mg, fentanyl 20 μg, and morphine 200 μg. Hypotension was treated with a phenylephrine infusion using a standardized algorithm (50 μg/min if SBP was 90%–99% of baseline, 100 μg/min for SBP 80%–89% baseline, and 200 μg/min plus boluses for SBP <80% baseline) for 15 minutes after the administration of spinal anesthesia. ADRB2 genotype at codons 16 and 27 was determined. The effect of genotype on administered phenylephrine was compared by analysis of variance and linear regression. RESULTS: Ninety-six women completed the protocol with full data available for analysis. In the unadjusted analysis, there were no significant differences in phenylephrine dose administered among different genotypes at codons 16 and 27. When adjusted for covariates (maternal body mass index, baseline systolic and diastolic blood pressure, neonatal weight, and ethnicity), there was an increase of 200 μg (95% confidence interval, 4–396; P = 0.04) in phenylephrine administered to Arg16 homozygous genotype subjects compared with Gly16 homozygous genotype subjects. CONCLUSIONS: Phenylephrine dose requirements to maintain SBP after spinal anesthesia are affected by ADRB2 genotype but to a lesser extent than ephedrine. This suggests that previous work demonstrating a large effect of ADRB2 genotype on ephedrine dose requirements may be explained, at least in part, by a differential response to ephedrine based on ADRB2 genotype. It also suggests that there may be ADRB2 -mediated differences in the physiologic response to spinal anesthesia. Abstract : Published ahead of print February 27, 2015